Pengaruh Konservatisme Akuntansi Dan Intensitas Modal Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia - Zulia Hanum; Rukmini Rukmini; Jasman Saripuddin Hasibuan (Jurnal Riset AKuntansi dan Bisnis, 2022)
This study aims to determine the effect of accounting conservatism and capital intensity on tax avoidance. Tax avoidance is the dependent variable in this study it is measured by the cash effective tax rate (CETR). The independents variables studied in this study are accounting conservatism and capital intensity. The type of research is associative research with a quantitative approach. Population in this study are pharmaceutical companies listed on the exchange Indonesia securities (IDX) year 2014-2019. The sample in the study was obtained using a purposive sampling method, so that we get 8 (eight) samples from 10 (ten) populations. The type of data in this study is secondary data which is tested using the classical assumption test method and hypothesis testing through the SPSS analysis program. The results of this study indicate that accounting conservatism and capital intensity have a simultaneous effect on tax avoidance. Partially accounting conservatism has no significant effect on tax avoidance. But, partially the capital intensity in this study has a significant effect on tax avoidance